Analysis Activity of Elephantopus scaber Leaves Extract Against Quantitative Changes of Lymphocytes Cells in BALB/c Mice After Induction of DMBA and Estrogen - Rochmatika, Lailiyavina; Widyarti, Sri; Djati, Muhammad Sasmito (The Journal of Experimental Life Science, 2019)
The carcinogenic compounds such as DMBA known for having the ability to promote the DNA damage that affects the growth regulator genes. Therefore, uncontrolled cell growth will occur and change the immune system. Elephantopus scaber extract is considered as an alternative way of handling breast cancer since it capable to affect the work of the immune system. Hence, this study aims to determine the effect of E. scaber extract on quantitative changes of CD4+, CD8+ T cells and proinflammatory cytokines CD4+IFNγ+ and CD4+TNF-α+ after induction of DMBA and estrogen. In vivo experiments were carried out by using 5-6 weeks old of female mice BALB/c strain. The extract of E. scaber leaf powder was obtained from Material Medica Batu, Malang. The experimental animals were divided into five groups such as negative control group (K-), positive control group (K+), mice treated with E. scaber extract for a week (group 1), mice treated with E. scaber extract for 2 weeks (group 2), and mice treated with E. scaber extract for 3 weeks (group 3). Induction of DMBA and estrogen was conducted by injection of DMBA (7.12 dimetylbenz (α) anthracene) 0.56 mg.kgBW-1 and estradiol hormone 0.0504 mg.kgBW-1. Mice were treated with E. scaber extract with a dose of 50 mg.kgBW-1. Lymphocytes were isolated from spleen and observed the CD4+, CD8+ T cells and proinflammatory cytokines CD4+IFN-γ+ and CD4+TNFα+ T cells through flow cytometry analysis. One-way ANOVA (p <0.05) and SPSS were used to analyze this data. The results showed that the induction of DMBA and estradiol hormone affected mice fur loss. It also decreased the immune system by lowering the number of CD4 and CD8 T cells. However, E. scaber extracts increased the number of pro-inflammatory cytokines TNF-α. Furthermore, the DMBA and estradiol induction also promoted the number of CD4+IFN-γ+ in the first week, but decreased the number of CD4+IFN-γ+ at weeks 2 and 3, then increase the number of CD4+IFN-γ+. So, the treatment of E. scaber extracts demonstrated the ability to restore the homeostasis of the immune system in the first and second weeks.  Keywords: CD4+, CD8+, DMBA, estrogen, E.scaber, IFN-γ+, TNF-α+